DETERMINANTS OF PROFESSIONAL INACTIVITY OF RETIREES LIVING RURAL AREAS OF THE EASTERN POLAND MACRO-REGION - Danuta Guzal-Dec; Agnieszka Siedlecka; Anna Jakubowicz (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the article is to identify the determinants of professional inactivity of retirees living in rural areas of the Eastern Poland macro-region. The method used was a literature review, document analysis and a survey using the survey technique conducted among 403 retirees receiving retirement benefits aged 60-69 (women) and 65-69 (men). About 60% of retirees living in the countryside only received retirement benefits and were not interested in working. In the case of retirees living in rural areas, compared to retirees living in cities, relatively greater barriers to taking up work were: lack of appropriate job offers, too high employer requirements, too low offered remuneration, health problems and a lower level of education. The study revealed the existence of statistically significant differences regarding the determinants of professional inactivity in the case of retirees living in rural areas and cities. The analysis of barriers to retirees staying on the labor market indicates the need for systemic support in the area of promoting employment, e.g. through financial support for recruiting companies, and on the other hand, activities activating seniors themselves. The high percentage of respondents who had unspecified plans after cessation of professional activity may indicate that these people could be more optimally “managed” on the labor market. Properly addressing activities supporting the use of the potential of older people requires a systematic diagnosis of resources and needs and monitoring the situation in the context of assessing the objective and subjective quality of life.